High prevalence of masked uncontrolled morning hypertension in elderly non‐valvular atrial fibrillation patients: Home blood pressure substudy of the ANAFIE Registry - Kazuomi Kario; Naoyuki Hasebe; Ken Okumura; Takeshi Yamashita; Masaharu Akao; Hirotsugu Atarashi; Takanori Ikeda; Yukihiro Koretsune; Wataru Shimizu; Hiroyuki Tsutsui; Kazunori Toyoda; Atsushi Hirayama; et al. (The Journal of Clinical Hypertension, 2021)
Abstract In the ANAFIE Registry home blood pressure subcohort, we evaluated 5204 patients aged ≥75 years with non‐valvular atrial fibrillation (NVAF) to assess blood pressure (BP) control, prevalence of masked hypertension, and anticoagulant use. Mean clinic (C) and home (H) systolic/diastolic BP(SBP/DBP) was 128.5/71.3 and 127.7/72.6 mm Hg, respectively. Overall, 77.5% of patients had hypertension; of these, 27.7%, 13.4%, 23.4%, and 35.6% had well‐controlled, white coat, masked, and sustained hypertension, respectively. Masked hypertension prevalence increased with diabetes, decreased renal function, age ≥80 years, current smoker status, and chronic obstructive pulmonary disease. By morning/evening average, 59.0% of patients had mean H‐SBP ≥ 125 mm Hg; 48.9% had mean C‐SBP ≥ 130 mm Hg. Early morning hypertension (morning H‐SBP ≥ 125 mm Hg) was found in 65.9% of patients. Although 51.1% of patients had well‐controlled C‐SBP, 52.5% of these had uncontrolled morning H‐SBP. In elderly NVAF patients, morning H‐BP was poorly controlled, and masked uncontrolled morning hypertension remains significant.